(untitled) (Bangladesh Veterinarian, 2024)
A Holstein-Friesian cross-bred cow was presented due to gestation being prolonged to >365 days. The presence of a dead fetus was determined by examination per rectum. Induction of parturition was attempted using dexamethasone and a PGF2α analogue, but the cow did not respond. The fetus was therefore removed two days later by caesarian surgery. The fetus had gross abnormalities of the head, but the brain was at least partially intact. The cow recovered uneventfully after surgery. It was considered that the gross prolongation of gestation was due to a developmental perturbation of the hypothalamo-pituitary-adrenal axis that had prevented the initiation of parturition. Bang. vet. 2024. Vol. 41, No. 1 – 2, 25 – 29